Investigation Of Torque And Flux-Current Producing Components In Indirect Rotor Flux Oriented Control (IRFOC) Of Induction Machines - Yusnida, Ahmad Tarmizi; Auzani, Jidin; Kasrul, Abdul Karim; Siti Azura, Ahmad Tarusan; Muhd Khairi, Abd Rahim; Sundram, Ramahlingam; Huzainirah, Ismail (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
This paper presents an investigation of torque and flux-current producing components in indirect rotor flux oriented control (IRFOC) of induction machine. Induction machine faced the problems when the motor rotates at the highest speed due to complex mathematical model based on the previous research. Therefore, to prove that there have the coupling effect, the investigation towards the torque and flux current component of IRFOC is done. The method that have been used to detect the problem is by using simulation method on MATLAB software. The algorithm and controller that been used is Field Oriented Control (FOC) because it is the first method in drive system that are been used in order to solve the induction machine problems. Simulation results presented in this paper show the torque, rotor flux, direct and quadrant current component when varying the value of torque and flux.